2014
DOI: 10.1364/ol.39.004978
|View full text |Cite
|
Sign up to set email alerts
|

Broadband electro-optical modulator based on transparent conducting oxide

Abstract: We report a broadband electro-optical (EO) modulator based on tunable plasmonic metamaterial. Transparent conducting oxides provide an excellent active plasmonic material for optoelectronic applications. By utilizing our indium-tin-oxide- (ITO) based multilayer structure, light absorption of the active ITO layer can be electrically modulated over a large spectrum range. Based on the attenuated total reflectance configuration, bias polarity-dependent modulation up to 37% has been experimentally demonstrated. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
43
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 58 publications
(43 citation statements)
references
References 20 publications
(23 reference statements)
0
43
0
Order By: Relevance
“…However, none of the experimental studies has reported the response of the modulators close to the upper limit (see table). A recently published study of dynamic tuning in multilayer structures shows the presence of a significant delay [111]. Thus, there is an urgent need for thorough experimental studies and advanced characterization of TCO-based devices, including the dynamic change of the applied voltage, highfrequency modulation of optical properties, determination of the upper limit of the modulation frequency, and the development of advanced theoretical models.…”
Section: Study Of Dynamic Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…However, none of the experimental studies has reported the response of the modulators close to the upper limit (see table). A recently published study of dynamic tuning in multilayer structures shows the presence of a significant delay [111]. Thus, there is an urgent need for thorough experimental studies and advanced characterization of TCO-based devices, including the dynamic change of the applied voltage, highfrequency modulation of optical properties, determination of the upper limit of the modulation frequency, and the development of advanced theoretical models.…”
Section: Study Of Dynamic Propertiesmentioning
confidence: 99%
“…The rapid energy transfer in the TCO produces a localized rise of the carrier temperature and increased carrier mobility, thus, providing a stronger nonlinear response. This ability to dramatically change the optical properties of TCOs from dielectric-like to metallic-like under an applied bias triggers new approaches for the realization of photonic modulators [110,111].…”
Section: Introductionmentioning
confidence: 99%
“…For example, in ref. 1 it was shown that a 10 nm thin ITO-layer is sufficient to build a modulator with 37% modulation depth for a wavelength of 1620 nm. The strong response was achieved by applying a voltage to the thin layer.…”
mentioning
confidence: 99%
“…Although the ITO plasma frequency is in the near-IR range [12,17,99,100], due to low losses, ITO could be used for plasmonic metamaterials in certain frequency ranges above the plasma frequency [10] and as an active material in plasmonic modulators [101][102][103][104] or as infrared antennae [105].…”
Section: Indium Tin Oxide Filmsmentioning
confidence: 99%